The State Structure Of Indigenous Communities In Timor-Leste (Empirical Legal Study in the Bunak Tribe, Bobonaro Municipality) - Tito Maia dos Reis (Fakultas Hukum, Universitas Warmadewa, 2025)
The formation of the state structure and government of the indigenous people of Timor-Leste is seen from a historical perspective before colonization, during colonization and after independence. The life of the indigenous people with their social structure is very strong, with two main problems being studied, namely: 1) the constitutional structure of Timor-Leste society based on customary law (2) the form of customary structure and function adopted in the RDTL constitution. This legal research is empirical research with a socio-legal research type focused on examining the application of customary norms, and looking at The State Structure Of Indigenous Communities In Timor-Leste (Empirical Legal Study In The Bunak Tribe, Bobonaro Municipality) law in the real sense and observe and examine how law works in society. In addition, this research uses a legal concept analysis approach (conceptual approach), a historical approach, and a comparative approach. The results of this thesis research indicate that the state structure and the government structure of indigenous peoples are the social structures of the indigenous people of Timor-Leste in the form of unwritten non-sctipta both the structure of authority, duties, and functions, as well as customary norms. Seen from the applicable legal norms of ius constitutum in the RDTL Constitution, the original state structure of Timor-Leste, along with its duties and functions, is still adopted.